Graduate grade inflation at a U.S. research-intensive university: A 22-year longitudinal analysis - Vivien Lee; Nathan R. Kuncel; Paul R. Sackett (PLoS ONE, 2026)
The phenomenon of grade inflation has been studied extensively at high school and undergraduate levels, yet little is known about its occurrence in graduate education. This study bridges this gap by examining graduate grade inflation using data from one U.S. research intensive university, covering two decades of admissions across 75 master’s programs ( N = 24,815) and 78 doctoral programs ( N = 15,701). Relying on both linear and ordinal multilevel models, we investigated the presence of grade inflation and potential variations by degree level and individual academic programs at the program level. Our findings provide preliminary evidence for the presence of graduate grade inflation and suggest that the magnitudes differ across individual academic programs. There is also evidence showing that the trend of grade inflation significantly differed across master’s and doctoral programs. This apparent inflation undermines the signaling value of grades for employers and admission decisions in the labor market and academic selection, as well as for research, feedback, and learning purposes. Future research should replicate our findings using multi-institutional samples and examine drivers of graduate grade inflation to more accurately estimate its magnitude.